Freaky peaks - Ganeri, Anita (Hippo London, 2001)
Provides miscellaneous facts about the world's mountains including, geological facts, information on the plants, animals and people that live there, mountain exploration and mountaineering, and their natural resources. Suggested level: primary, intermediate